Midwives’ Experiences of Rural Maternal - Newborn Care in Ghana: A Phenomenological Inquiry - Mary Ani-Amponsah; Solina Richter (Online Journal of Rural Nursing and Health Care, 2021)
Midwives’ experiences of frontline healthcare delivery in rural maternal and newborn care have been minimally explored over the past two decades in low and middle-income countries but particularly in resource-limited settings, the situation is concerning. Understanding the dynamic influences that impact health care delivery in rural and remote settings is important for averting deaths, improving health outcomes and rural health care practice.